Chemoradiotherapy with or without cetuximab in patients with oesophageal cancer (SCOPE1): a multicentre, phase 2/3 randomised trial. - Crosby, T; Hurt, C; Falk, S; Gollins, S; Mukherjee, S; Staffurth, J; Ray, R; Bashir, N; Bridgewater, J; Geh, J; Cunningham, D; Blazeby, J; et al. (2013)
BACKGROUND: Definitive chemoradiotherapy (CRT) is an alternative to surgery for the curative treatment of oesophageal carcinoma. The SCOPE1 trial aimed to investigate the addition of cetuximab to cisplatin and fluoropyrimidine-based definitive CRT in patients with localised oesophageal squamous-cell cancer and adenocarcinomas to assess activity, safety, and feasibility of use. METHODS: In this multicentre, randomised, open-label, phase 2/3 trial, we recruited patients aged 18 years and older from UK radiotherapy centres who had non-metastatic, histologically confirmed carcinoma of the oesophagus (adenocarcinoma, squamous-cell, or undifferentiated; WHO status 0-1; stage I-III disease) and been selected to receive definitive CRT. Patients were randomly assigned (1:1) via a central computerised system using stratified minimisation (with an 80:20 random element) to receive CRT alone or CRT with cetuximab (400 mg/m(2) on day 1 followed by 250 mg/m(2) weekly), stratified by recruiting hospital, primary reason for not having surgery, tumour histology, and tumour stage. CRT consisted of cisplatin 60 mg/m(2) (day 1) and capecitabine 625 mg/m(2) twice daily (days 1-21) for four cycles; cycles three and four were given concurrently with 50 Gy in 25 fractions of radiotherapy. The primary endpoint was the proportion of patients who were treatment failure free at week 24 for the phase 2 trial and overall survival for the phase 3 trial, both measured from randomisation. We analysed data by intention to treat. This trial is an International Standard Randomised Controlled Trial, number 47718479. FINDINGS: 258 patients (129 assigned to each treatment group) from 36 UK centres were recruited between Feb 7, 2008, and Feb 22, 2012. Recruitment was stopped without continuation to phase 3 because the trial met criteria for futility, but we continued to follow-up recruited patients until all had reached at least 24-week follow-up (median follow-up of patients who survived was 16.8 months [IQR 11.2-24.5]). Fewer patients were treatment failure free at 24 weeks in the CRT plus cetuximab group (79 of 119 patients [66·4%, 90% CI 58·6-73·6]) than in the CRT only group (93 of 121 patients [76.9%, 69.7-83.0]). The CRT plus cetuximab group also had shorter median overall survival (22.1 months [95% CI 15.1-24.5] vs 25.4 months [20.5-37.9]; adjusted HR 1.53 [95% CI 1.03-2.27]; p=0.035). Patients who received CRT plus cetuximab had more non-haematological grade 3 or 4 toxicities (102 [79%] of 129 patients vs 81 [63%] of 129 patients; p=0.004). The most common grade 3 or 4 toxicities were low white blood cell count (14 [11%] in the CRT plus cetuximab group vs 21 [16%] in the CRT only group), low absolute neutrophil count (15 [12%] vs 24 [19%]), fatigue (26 [20%] vs 25 [19%]), and dysphagia (35 [27%] vs 37 [29%]). INTERPRETATION: The addition of cetuximab to standard chemotherapy and radiotherapy cannot be recommended for patients with oesophageal cancer suitable for definitive CRT. FUNDING: Cancer Research UK.